STRATEGI PENINGKATAN KOMPETENSI PENDIDIKAN MELALUI MANAGEMEN BERBASIS SEKOLAH - Mukarromah, Siti Baitul (Lembaran Ilmu Kependidikan, 2009)
Paradigm shift in education which resulted in the change of role of educationalinstitution from non profit social institutions to profit enterprises indicates amanagement change. The change requires a management improvement to enable theeducational institution to sustain and develop. Based on the future needs, eacheducational institution should reform or transform itself to answer the demands of thesociety in general and labor market in particular. In line with the paradigm shift, thisarticle discusses the need to improve educational management from seven aspects: (a)knowledge, (b) technology, (c) power, (d) material, (e) people, (F) time and (g)finance.Kata kunci : strategi, pendidikan, dan managemen berbasis sekolah